Endocrine, auxological and metabolic profile in children and adolescents with Down syndrome: from infancy to the first steps into adult life - Molinari, Silvia; Fossati, Chiara; Nicolosi, Maria Laura; Di Marco, Santo; Faraguna, Martha Caterina; Limido, Francesca; Ocello, Laura; Pellegrinelli, Claudia; Lattuada, Martina; Gazzarri, Alessandra; Lazzerotti, Alessandra; Sala, Debora; et al. (Frontiers in Endocrinology, 2024)
Down syndrome (DS) is the most common chromosomal disorder worldwide. Along with intellectual disability, endocrine disorders represent a remarkable share of the morbidities experienced by children, adolescents and young adults with DS. Auxological parameters are plotted on syndrome-specific charts, as growth rates are reduced compared to healthy age- and gender-matched peers. Furthermore, children with DS are at increased risk for thyroid dysfunctions, diabetes mellitus, osteopenia and obesity compared to general population. Additionally, male individuals with DS often show infertility, while women tend to experience menopause at an overall younger age than healthy controls. Given the recent outstanding improvements in the care of severe DS-related comorbidities, infant mortality has dramatically decreased, with a current average life expectancy exceeding 60 years. Accordingly, the awareness of the specificities of DS in this field is pivotal to timely detect endocrine dysfunctions and to undertake a prompt dedicated treatment. Notably, best practices for the screening and monitoring of pediatric endocrine disorders in DS are still controversial. In addition, specific guidelines for the management of metabolic issues along the challenging period of transitioning from pediatric to adult health care are lacking. By performing a review of published literature, we highlighted the issues specifically involving children and adolescent with DS, aiming at providing clinicians with a detailed up-to-date overview of the endocrine, metabolic and auxological disorders in this selected population, with an additional focus on the management of patients in the critical phase of the transitioning from childhood to adult care.